2022
DOI: 10.1172/jci150101
|View full text |Cite
|
Sign up to set email alerts
|

Platelets mediate inflammatory monocyte activation by SARS-CoV-2 spike protein

Abstract: Infection with SARS-CoV-2, the causative agent of COVID-19, causes mild to moderate disease in most patients but carries a risk of morbidity and mortality.Seriously affected individuals manifest disorders of hemostasis and a cytokine storm, but it is not understood how these manifestations of severe COVID-19 are linked. Here, we showed that the SARS-CoV-2 Spike protein engaged the CD42b receptor to activate platelet via two distinct signaling pathways, and promoted platelet-monocyte communication through the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 47 publications
(56 reference statements)
3
64
0
2
Order By: Relevance
“…In vitro infection of platelets from healthy volunteers shows that platelets recognize and respond to SARS‐CoV‐2 becoming activated 21,28,41,42 . Similar results have been observed in platelets exposed to recombinant Spike protein and Spike‐containing pseudovirus 21,41,43 . SARS‐CoV‐2‐induced platelet activation in vitro is inhibited by competition with recombinant ACE‐2, suggesting platelet activation through the Spike receptor‐binding domain 41 .…”
Section: Platelet Activation and Hyperresponsiveness In Covid‐19 Hype...supporting
confidence: 69%
See 3 more Smart Citations
“…In vitro infection of platelets from healthy volunteers shows that platelets recognize and respond to SARS‐CoV‐2 becoming activated 21,28,41,42 . Similar results have been observed in platelets exposed to recombinant Spike protein and Spike‐containing pseudovirus 21,41,43 . SARS‐CoV‐2‐induced platelet activation in vitro is inhibited by competition with recombinant ACE‐2, suggesting platelet activation through the Spike receptor‐binding domain 41 .…”
Section: Platelet Activation and Hyperresponsiveness In Covid‐19 Hype...supporting
confidence: 69%
“…19 Platelets activated by SARS-CoV-2 Spike protein also bind to monocytes through P-selectin and CD40-L, and signal proinflammatory monocyte activation with high IL-1β expression. 43 Similarly, results from our group show that platelets from COVID-19 patients or in vitro-infected platelets also induce a proinflammatory program in monocytes, which is induced by P-selectin and integrin α IIb /β 3 binding and is amplified by TF signaling. 46 Platelet activation and monocyte TF expression positively correlate with plasma levels of D-dimers, supporting a role in hypercoagulability.…”
Section: Pl Atele T-leuko C Y Te Inter Ac Ti On In Covid -19 Hypercoa...mentioning
confidence: 64%
See 2 more Smart Citations
“…Interestingly they observed that the soluble CD40L plasma level decreased overtime while that of sCD62P increased significantly, highlighting the importance of the inflammatory kinetics in COVID-19. Finally, Tianyang Li et al (140) have defined a mechanism that may be a potential therapeutic target in severe COVID-19. They showed that hypercoagulation and the cytokine storm in severe COVID-19 were linked through the Spike-CD42b interaction that activates platelets, the CD40L-CD40 and the P-selectin-PSGL-1 interactions that bind them to monocytes, and the strong induction of IL-1b in monocytes.…”
Section: In An Infectious Contextmentioning
confidence: 99%